2020
DOI: 10.1016/j.paerosci.2019.100596
|View full text |Cite
|
Sign up to set email alerts
|

Transonic aeroelasticity: A new perspective from the fluid mode

Abstract: Within the transonic regime, the aeroelastic problems exhibit many unique characteristics compared with subsonic and supersonic cases. Although a lot of research has been carried out in this field, the underlying mechanisms of these complex phenomena are not clearly understood yet, resulting in a challenge in the design and use of modern aircraft. This review summarizes the recent investigations on nonclassical transonic aeroelastic problems, including transonic buzz, reduction of transonic buffet onset, trans… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 111 publications
1
14
0
Order By: Relevance
“…A similar resonance effect has been reported and described on spring-mounted circular cylinder flows, based on stability analysis 38,40,72 and nonlinear temporal simulations 35,39,40 . More recently similar phenomena were highlighted for spring-mounted airfoils undergoing tran-sonic buffet flow conditions 42,43 .…”
Section: B Effect Of the Reduced Velocitysupporting
confidence: 52%
See 1 more Smart Citation
“…A similar resonance effect has been reported and described on spring-mounted circular cylinder flows, based on stability analysis 38,40,72 and nonlinear temporal simulations 35,39,40 . More recently similar phenomena were highlighted for spring-mounted airfoils undergoing tran-sonic buffet flow conditions 42,43 .…”
Section: B Effect Of the Reduced Velocitysupporting
confidence: 52%
“…This framework was first extended to fluid-solid interaction problems to investigate the vortex-induced vibrations of spring-mounted rigid cylinders in low-Reynoldsnumber flows [38][39][40][41] . More recently, it was used to predict the transonic shock buffeting instability of springmounted airfoils 42,43 . Other possible applications are the study of path instabilities of freely falling or rising rigid objects [44][45][46] or of the onset of pitch-oscillations on airfoils at transitional Reynolds numbers 47 .…”
Section: Introductionmentioning
confidence: 99%
“…The outputs of a linear ROM modelling transonic buffet flow over a NACA0012 airfoil were compared with the outputs of a full-order model from CFD/CSD simulation by Gao, Zhang & Li (2019), and it was found that the outputs of the ROM compared well with those of the full-order models. An additional advantage of using ROMs is that the coupled patterns between the fluid mode and structural mode in unsteady flow can be clearly captured (Gao & Zhang 2020). Other studies of ROMs on unsteady flow include the development of ROMs for the analysis of vortex-induced vibrations about a long flexible cylinder in both the in-line and cross-flow directions.…”
Section: Introductionmentioning
confidence: 99%
“…Hazardous aeroelastic phenomena such as flutter may arise from this higher flexibility in the flight envelope. Hence, the importance of studying aircraft aeroelastic behavior computationally and devising sub-scale models that are representative of the aeroelastic behavior of full size wing designs to enable the study of these new designs [10][11][12].…”
Section: Introductionmentioning
confidence: 99%